MOMODI: MOBILE MODUL BERMUATAN KEARIFAN LOKAL DALAM PEMBELAJARAN TEKS DESKRIPTIF BAHASA INDONESIA SISWA KELAS V (STUDI ANALISIS KEBUTUHAN DAN DESAIN) - Muhammad Noor Alfiandi; Erik Aditia Ismaya; Muhammad Noor Ahsin; Rani Setiawaty (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the needs and design the development of a mobile descriptive text module based on local wisdom in Kudus for Indonesian language learning at SD 2 Kesambi. Data were collected through interviews with fifth-grade teachers and questionnaires administered to 28 students. The results showed that the learning media used were still limited to textbooks, blackboards, and simple pictures, making learning less interesting and unable to help students determine objects for description, choose diction, and understand text structure coherently. Teachers stated the need for interactive mobile-based digital media that display Kudus cultural objects to make learning more contextual and motivate students. The questionnaire data reinforced this need, with 71.43% of students still having difficulty understanding descriptive texts, 78.57% easily bored with textbooks, and 96.43% very interested in using mobile media, while local cultural knowledge was only 42.86%. Based on these findings, this study produced a preliminary design for the MOMODI mobile module, which includes learning objectives, concept maps, text and video materials, examples of local cultural descriptions, interactive exercises, and gamification, designed using Canva, Heyzine, and APPSGEYSER.